2011
DOI: 10.1016/j.juro.2011.03.156
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Late Maturation Arrest: Reproductive Outcomes of Testicular Failure

Abstract: Purpose There is a paucity of data characterizing infertile men with maturation arrest. We hypothesized that men with early stage maturation arrest could be clinically distinguished from men with late maturation arrest and would have worse reproductive outcomes. Materials and Methods We retrospectively reviewed the records of all patients with nonobstructive azoospermia and cryptozoospermia who underwent testis mapping and sperm extraction from 2002 to 2009 and for whom histopathological findings were availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 27 publications
(31 reference statements)
3
36
0
Order By: Relevance
“…Although studies are lacking to assess the early phase of spermatogenesis up to pachytene, earlier studies showed up to 50% reduced recombination rates in cases with MA (Gonsalves et al 2004, Egozcue et al 2005. Similarily, a sixfold increased frequency of genetic abnormalities was observed in cases of MA compared with Hyp (Weedin et al 2011).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although studies are lacking to assess the early phase of spermatogenesis up to pachytene, earlier studies showed up to 50% reduced recombination rates in cases with MA (Gonsalves et al 2004, Egozcue et al 2005. Similarily, a sixfold increased frequency of genetic abnormalities was observed in cases of MA compared with Hyp (Weedin et al 2011).…”
Section: Discussionmentioning
confidence: 78%
“…In addition, in cases with MA reduced recombination rates (up to 50%) were found (Gonsalves et al 2004, Egozcue et al 2005 and an increased frequency of genetic abnormalities (Weedin et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…In our study, multiple TESE, including contralateral sampling in hypospermatogenesis and in adverse histopathology patterns (MA and SCO), was associated with a higher SRR (Table 3). According to Weedin et al, 2011, when subjects with uniform MA were subcategorized in early and late MA, the latter reported a significantly higher SRR during c-TESE (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…We reconciled the absence of diagnostic biopsies by subcategorizing our population into NOA with an elevated FSH, as can be seen in Sertoli Cell Only syndrome and early maturation arrest, and NOA with normal FSH which is most often associated with late maturation arrest as suggested by Lipshultz [25] . He found that men with late maturation arrest, in which spermatids are present, had decreased FSH and a higher TESE sperm retrieval rate compared to those with early maturation arrest, in which primarily spermatogonia or spermatocytes were seen [25] .…”
Section: Discussionmentioning
confidence: 99%
“…He found that men with late maturation arrest, in which spermatids are present, had decreased FSH and a higher TESE sperm retrieval rate compared to those with early maturation arrest, in which primarily spermatogonia or spermatocytes were seen [25] .…”
Section: Discussionmentioning
confidence: 99%